Emerging role of ferroptosis-related circular RNA in tumor metastasis - Meng, Yifei; Cao, Jingdong; Li, Yidan; Duan, Saili; Zhou, Zongjiang; Li, Jinghe; Ousmane, Diabate; Ou, Chunlin; Wang, Junpu (Frontiers in Pharmacology, 2023)
Tumor metastasis is an important factor that contributes to the poor prognosis of patients with tumors. Therefore, to solve this problem, research on the mechanism of metastasis is essential. Ferroptosis, a new mode of cell death, is characterized by membrane damage due to lipid peroxidation caused by iron overload. Many studies have shown that excessive ferroptosis can affect tumor metastasis and thus inhibit tumor progression. Recently, circular RNA (circRNA), a type of non-coding RNA, has been shown to be associated with the progression of ferroptosis, thus influencing tumor development. However, the specific mechanisms by which circRNAs affect the progression of ferroptosis and their roles in tumor metastasis are not known. In this review, we systematically discuss the role of circRNAs in regulating tumor ferroptosis and their mechanism of action through sponging miRNAS in various tumors, thereby impacting metastasis. This review helps elucidate the relationship and role of ferroptosis-related circRNAs in tumor metastasis and may provide future researchers with new ideas and directions for targeted therapies.